Clinical diversity of ankylosing spondylitis in the real practice of a rheumatologist in Russia (Part 1) - Evgeny Vladimirovich Volnukhin; E A Galushko; A G Bochkova; A V Smirnov; Sh F Erdes (Научно-практическая ревматология)
Objective: to study the clinical picture of ankylosing spondylitis (AS), the association of its manifestations with the degree of disability in the real practice of a rheumatologist in Russia. Subjects and methods. The investigation enrolled 464 patients with AS, who had consecutively visited rheumatologists for 4 months in 24 cities and towns of the Russian Federation. A specially designed clinical card was filled out for all patients. Later on, the diagnosis of the disease was verified at the Research Institute of Rheumatology, Russian Academy of Medical Sciences, according to the 1984 modified New York criteria and pelvic survey X-ray films were assessed by two independent experts in a blind fashion. Results. The valid diagnosis of AS was confirmed in 330 (71.1%) out of all 464 patients included into the study; their mean age was 39.7±10.2 years; the mean duration of disease was 14.6±2.6 years; 86% were men and 14% were women. About half (47%) of the patients had peripheral arthritis and 56% had clinical signs of coxitis. The mean BASDAI and BASFI scores were 4.8±2.1 and 4.3±2.6, respectively. 61% of the patients had a BASDAI score of >4.0. Uveitis was the most common extravertebral manifestation (22%). One third of the patients did not work because of health reasons; 45% of the patients changed their work activities due to disease. Conclusion. In Russia, AS is characterized by its high activity, frequent involvement of hip joints and poor functional status in the patients on average 15 years after the onset of the disease. Loss of working capacity was observed in one-third of the patients. In the country, AS is diagnosed very late, on average 9 years after the disease onset.